2019
DOI: 10.5751/es-11039-240335
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the usefulness of scenario archetypes in science-policy processes: experience across IPBES assessments

Abstract: Scenario analyses have been used in multiple science-policy assessments to better understand complex plausible futures. Scenario archetype approaches are based on the fact that many future scenarios have similar underlying storylines, assumptions, and trends in drivers of change, which allows for grouping of scenarios into typologies, or archetypes, facilitating comparisons between a large range of studies. The use of scenario archetypes in environmental assessments foregrounds important policy questions and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The food will be shared within the community and there will be no food wastage. were analysed for commonalities and differences and then compared to existing scenarios archetypes that were used in the IPBES regional assessments (See Sitas et al 2019). We used keywords or phrases as indicators to identify themes or points in common between the four groups and also discussed how the visions contribute to ongoing debates about pathways towards more desirable futures by referencing where they speak to existing recommendations (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The food will be shared within the community and there will be no food wastage. were analysed for commonalities and differences and then compared to existing scenarios archetypes that were used in the IPBES regional assessments (See Sitas et al 2019). We used keywords or phrases as indicators to identify themes or points in common between the four groups and also discussed how the visions contribute to ongoing debates about pathways towards more desirable futures by referencing where they speak to existing recommendations (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…We contextualized the four visions within the scenario archetypes used in the IPBES regional assessment process to synthesise and harmonise the analysis of existing regional and global scenarios (See Sitas et al 2019). As this was such an important organising principle for IPBES scenarios work, it is important to see what additional contributions this visioning process based on the Nature Futures Framework can make for future assessments.…”
Section: Archetypesmentioning
confidence: 99%
“…An early example is the work of the Global Scenarios Group and its successor, the Great Transition Initiative (229). More recent work is reflected in the creative use of imagination-driven scenarios in the Millennium Ecosystem Assessment and its successor, the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) (230).…”
Section: Transformations To What? Integrating Anticipation and Imagination Transformations To What?mentioning
confidence: 99%
“…Other papers identify whole suites of archetypes through meta-studies of secondary sources (Gotgelf et al 2020, Horcea-Milcu et al 2020, Tribaldos et al 2020. A further set of papers use archetypes in a deductive way to design or analyze scenarios (Harrison et al 2019, Sitas et al 2019. Neudert et al (2019) start from a suite of archetypes identified in earlier studies in order to refine them, to diagnose patterns in a new set of cases, and to dig deeper into selected archetypes.…”
Section: Special Feature On Archetype Analysis In Sustainability Researchmentioning
confidence: 99%
“…Fourth, scenario archetypes have supported science-policy dialogues such as in the Intergovernmental Science-Policy Platform for Biodiversity and Ecosystem Services in multiple fruitful ways. The studies suggest that a next generation of scenario archetypes might be more inductive and consider linkages of scenarios across scales in a more detailed way (Harrison et al 2019, Sitas et al 2019.…”
Section: Special Feature On Archetype Analysis In Sustainability Researchmentioning
confidence: 99%